On The Current State of Scholarly Retrieval Systems - Khalid, S.; Khusro, S.; Ullah, I.; Dawson-Amoah, G. (Engineering, Technology & Applied Science Research, 2019)
The enormous growth in the size of scholarly literature makes its retrieval challenging. To address this challenge, researchers and practitioners developed several solutions. These include indexing solutions e.g. ResearchGate, Directory of Open Access Journals (DOAJ), Digital Bibliography & Library Project (DBLP) etc., research paper repositories e.g. arXiv.org, Zenodo, etc., digital libraries, scholarly retrieval systems, e.g., Google Scholar, Microsoft Academic Search, Semantic Scholar etc., digital libraries, and publisher websites. Among these, the scholarly retrieval systems, the main focus of this article, employ efficient information retrieval techniques and other search tactics. However, they are still limited in meeting the user information needs to the fullest. This brief review paper is an attempt to identify the main reasons behind this failure by reporting the current state of scholarly retrieval systems. The findings of this study suggest that the existing scholarly retrieval systems should differentiate scholarly users from ordinary users and identify their needs. Citation network analysis should be made an essential part of the retrieval system to improve the search precision and accuracy. The paper also identifies several research challenges and opportunities that may lead to better scholarly retrieval systems.